Effects of Using Personal Genotype Data on Student Learning and Attitudes in a Pharmacogenomics Course - Weitzel, Kristin Wiisanen (Am J Pharm Educ, 2016)
Objective. To evaluate the impact of personal genotyping and a novel educational approach on student attitudes, knowledge, and beliefs regarding pharmacogenomics and genomic medicine. Methods. Two online elective courses (pharmacogenomics and genomic medicine) were offered to student pharmacists at the University of Florida using a flipped-classroom, patient-centered teaching approach. In the pharmacogenomics course, students could be genotyped and apply results to patient cases. Results. Thirty-four and 19 student pharmacists completed the pharmacogenomics and genomic medicine courses, respectively, and 100% of eligible students (n=34) underwent genotyping. Student knowledge improved after the courses. Seventy-four percent (n=25) of students reported better understanding of pharmacogenomics based on having undergone genotyping. Conclusions. Completion of a novel pharmacogenomics elective course sequence that incorporated personal genotyping and genomic medicine was associated with increased student pharmacist knowledge and improved clinical confidence with pharmacogenomics.